2019
DOI: 10.1111/pedi.12871
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes, care utilization, and expenditures in adolescent pregnancy complicated by diabetes

Abstract: Background and Objective Adolescence and pregestational diabetes separately increase risks of adverse pregnancy outcomes, but little is known about their combined effect. To analyze pregnancy outcomes, healthcare utilization, and expenditures in adolescent pregnancies with and without pregestational diabetes using a national claims database. Methods Retrospective study using Truven Health MarketScan Commercial Claims and Encounters Database, 2011 to 2015. Females 12 to 19 years old, continuously enrolled for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Comparisons between groups were made using χ 2 testing and the resulting p values are shown ND, not determined (number suppressed as fewer than 5 per cell or would allow a value of less than 5 to be calculated) increased pregnancy complication rates compared with teenagers without diabetes [16]. Consistent with our findings, the researchers reported an increased risk of pre-eclampsia, preterm delivery and high birthweight [16]. However, they did not differentiate between types of pregestational diabetes and no socioeconomic data were included.…”
Section: Data Are N (%)mentioning
confidence: 99%
See 1 more Smart Citation
“…Comparisons between groups were made using χ 2 testing and the resulting p values are shown ND, not determined (number suppressed as fewer than 5 per cell or would allow a value of less than 5 to be calculated) increased pregnancy complication rates compared with teenagers without diabetes [16]. Consistent with our findings, the researchers reported an increased risk of pre-eclampsia, preterm delivery and high birthweight [16]. However, they did not differentiate between types of pregestational diabetes and no socioeconomic data were included.…”
Section: Data Are N (%)mentioning
confidence: 99%
“…The published literature on pregnancy outcomes in teenagers with type 1 diabetes is limited. A recently published study of pregnancy outcomes in teenagers with pregestational diabetes reported that adverse outcomes are more common in teenagers with pregestational diabetes than in teenagers without diabetes, but did not compare outcomes between teenagers with diabetes and older women with diabetes [16]. The largest published study to date comparing outcomes in teenagers and older women with type 1 diabetes included just 18 teenage pregnancies, and suggested that the children of teenagers with type 1 diabetes are at higher risk of congenital malformations [17].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has also shown more frequent hospital admissions of the offspring of adolescents with type 1 diabetes (T1D) in the first year after delivery 15 . Pregnancy in adolescents with diabetes has a worse outcome than pregnancy in adult women with T1D and in adolescents without diabetes, which highlights the importance of pregnancy prevention in young women with diabetes 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…15 Pregnancy in adolescents with diabetes has a worse outcome than pregnancy in adult women with T1D and in adolescents without diabetes, which highlights the importance of pregnancy prevention in young women with diabetes. 16,17 Maternal hyperglycemia during pregnancy is harmful to both the mother and the fetus and has a central role in the explanation of complications of pregnancy in women with diabetes. Therefore, the recommendation is to achieve an HbA1c level of ≤6.5% in the months T A B L E 1 Pregnancy rates of the different contraceptive alternatives for adolescents Note: Efficacy is shown as the Pearl Index, which is defined as the number of pregnancies in 100 women during one year of exposure or the proportion of women who experienced an unintended pregnancy within the first year of use.…”
mentioning
confidence: 99%
“…14,15 Although adolescent deliveries have decreased over recent decades, 16 there are few data on recent comorbidity and adverse outcomes trends specifically among adolescents. 17,18 Older research supported that adolescent deliveries were associated with increased risk for a range of adverse outcomes. [19][20][21] Further characterization of underlying comorbidity and risk among adolescent deliveries may be of public health importance.…”
mentioning
confidence: 99%